The Meaning of Lyric Pamer Bojo By Alm. Didi Kempot - Roro Ayu; Didik Hariyanto (Indonesian Journal of Cultural and Community Development, 2022)
Didi Kempot who is better known as "The Godfather of Broken Heart" is one of the singers who makes campursari songs liked by all people. The song, entitled Pamer Bojo, makes young people love the Javanese campursari music genre. This phenomenon is interesting because more than 90% of the audience for this song are young people. The purpose of this study is to find out the meaning contained in the lyrics of the song Pamer Bojo so that it can embrace all ages. This study uses the analysis method of Roland Barthes by looking for denotations, connotations and myths. The results of this study indicate that the meaning of the lyrics of the song Pamer Bojo is representative of the pain of being left by his lover. An ex-lover's arrogance with a new partner makes the heartache worse. All ages have the potential to experience this heartache, including young people. Although the lyrics of the song Pamer Bojo are in Javanese, this song can still convey the message in the lyrics of the song well.